2023
DOI: 10.1002/smll.202206229
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ Assembled Trapping Gel Repairs Spinal Cord Injury by Capturing Glutamate and Free Calcium Ions

Abstract: Increased glutamate (Glu) and free calcium ions are two major factors contributing to secondary injuries. Glu is the most abundant excitatory neurotransmitter that can lead to the hyperexcitability of adjacent neurons. [4] Hyperexcited neurons cause persistent pain in patients. [5] Various studies have identified Glu inhibition as an important therapeutic strategy for SCI. For example, multiple intrathecal injections of neuregulin-1 beta1 could protect spinal cord-injured neurons from Glu-induced excitotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…As shown in Figure A, a total of 152 genes were upregulated and 157 genes were downregulated in the Ri@EGCG-2 NP group compared with the SCI group. Remarkably, among the upregulated genes in the Ri@EGCG-2 NP group, there were numerous genes related to SCI repair including nerve regeneration, synaptic remodeling, and extracellular mechanism remodeling (Figure B), such as Galr2, Mospd4, Lilrb3a, Col22a1, Col2a1, etc. Similarly, the significant enrichments in Gene Ontology (GO) biological processes (BP), molecular function (MF), and cellular component (CC) (Figure C, Figures S16 and S17) showed that the pathways related to stem cell proliferation, axon regeneration, neuron regeneration, synaptic remodeling, and extracellular matrix remodeling were significantly enriched in the Ri@EGCG-2 NPs group compared with the SCI group. To confirm the results of RNA sequencing, sections and immunofluorescence staining were performed on the spinal cord tissue at the injury site. As shown in the immunofluorescence staining with DAPI and Nestin (to label neural stem cells (NSCs)) images in Figure D and quantitative analysis in Figure E, there was a small amount of Nestin-positive NSCs in SCI groups, and more noticeable Nestin-positive NSCs filled the injury site in the Ri@EGCG-2 NPs group.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure A, a total of 152 genes were upregulated and 157 genes were downregulated in the Ri@EGCG-2 NP group compared with the SCI group. Remarkably, among the upregulated genes in the Ri@EGCG-2 NP group, there were numerous genes related to SCI repair including nerve regeneration, synaptic remodeling, and extracellular mechanism remodeling (Figure B), such as Galr2, Mospd4, Lilrb3a, Col22a1, Col2a1, etc. Similarly, the significant enrichments in Gene Ontology (GO) biological processes (BP), molecular function (MF), and cellular component (CC) (Figure C, Figures S16 and S17) showed that the pathways related to stem cell proliferation, axon regeneration, neuron regeneration, synaptic remodeling, and extracellular matrix remodeling were significantly enriched in the Ri@EGCG-2 NPs group compared with the SCI group. To confirm the results of RNA sequencing, sections and immunofluorescence staining were performed on the spinal cord tissue at the injury site. As shown in the immunofluorescence staining with DAPI and Nestin (to label neural stem cells (NSCs)) images in Figure D and quantitative analysis in Figure E, there was a small amount of Nestin-positive NSCs in SCI groups, and more noticeable Nestin-positive NSCs filled the injury site in the Ri@EGCG-2 NPs group.…”
Section: Resultsmentioning
confidence: 95%
“…The intracellular homeostasis is disrupted after SCI, characterized by increased excitotoxicity of glutamate, elevated levels of free iron, and increased membrane permeability of Ca 2+ ( 21 ). The elevated intracellular Ca 2+ levels activate the nicotinamide adenine dinucleotide, which promotes ATP production while also increasing the production of ROS ( 22 , 23 ). Excessive ROS can increase the permeability of Ca 2+ membranes, leading to an increased influx of Ca 2+ , which causes a decrease in membrane potential.…”
Section: The Relationship Between Sci With Oxidative Stressmentioning
confidence: 99%
“…In a recent study, Huang et al developed an in situ assembled trapping gel composed of recombinant glutamate decarboxylase 67 (rGAD67) protein, alginate, and temperature-sensitive Pluronic F-127 for the direct elimination of glutamate (Glu) and free Ca 2+ released from injured cells during spinal cord injury (SCI) secondary damage [ 150 ]. Following intrathecal administration, Pluronic F-127 promoted in situ gelation while free Ca 2+ auto-exchanged with Na + from sodium alginate to form gellable calcium alginate.…”
Section: Application Of Marine Organisms-derived Polysaccharide Nanom...mentioning
confidence: 99%